2000
DOI: 10.1055/s-0037-1614108
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Endothelial Cell Markers in Primary Antiphospholipid Syndrome

Abstract: SummaryThe pathogenic mechanism underlying the prothrombotic tendency of Hughes’ or antiphospholipid syndrome (APS) has not been elucidated. Numerous procoagulant mechanisms have been tested including platelet activation, monocyte tissue factor (TF) expression and endothelial cell (EC) activation. There is some evidence for the latter from studies on cultured human umbilical vein endothelial cells (HUVEC). Incubation with antiphospholipid antibodies (aPL) induces EC activation in vitro. We investigated whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
60
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 35 publications
9
60
0
1
Order By: Relevance
“…Furthermore, they are consistent with studies of human subjects showing evidence of activation of the endothelium in APS: endothelial cell microparticles, soluble VCAM1, soluble ICAM-1, von Willebrand factor, soluble thrombomodulin, and soluble P-selectin. [53][54][55][56] Our results confirm that endothelium activation is enhanced in the presence of aPL antibodies but demonstrate that enhancement is platelet thrombusdependent. By visualization of the targets of the anti-b2GP1 autoantibody/b2GP1 complex and the functional implications of anti-b2GP1 autoantibody/b2GP1 complex binding to that target, we establish important features of the pathogenesis of aPL autoantibodies.…”
supporting
confidence: 67%
“…Furthermore, they are consistent with studies of human subjects showing evidence of activation of the endothelium in APS: endothelial cell microparticles, soluble VCAM1, soluble ICAM-1, von Willebrand factor, soluble thrombomodulin, and soluble P-selectin. [53][54][55][56] Our results confirm that endothelium activation is enhanced in the presence of aPL antibodies but demonstrate that enhancement is platelet thrombusdependent. By visualization of the targets of the anti-b2GP1 autoantibody/b2GP1 complex and the functional implications of anti-b2GP1 autoantibody/b2GP1 complex binding to that target, we establish important features of the pathogenesis of aPL autoantibodies.…”
supporting
confidence: 67%
“…Utilizing ICAM-1, E-selectin, and P-selectin knock-out mice and specific anti-VCAM-1 monoclonal antibodies, we demonstrated that EC-activating properties of aPL are mediated by these CAMs [13,14]. Accordingly, some investigators have shown increased levels of soluble adhesion molecules such as VCAM-1 and P-selectin in patients with aPL and thrombosis [15,16].…”
Section: Effects Of Apl On Ecsmentioning
confidence: 85%
“…Different indirect parameters of EC perturbation ex-vivo have been investigated with no definite conclusions. While some studies reported increased plasma levels of single soluble ADM or endothelial derived microparticles in APS patients, others did not confirm these findings [36][37][38][39]. Additional confounding variables-such as a concomitant associated immune-mediated systemic inflammatory disorder-did weaken the comparison.…”
Section: Do Apl Induce An Endothelial Perturbation In Vivo Too?mentioning
confidence: 91%